Exploring the Relationship between Academic Engagement and Achievement among Nursing Students of Ilam University of Medical Sciences - Jamil Sadeghifar; Mohammadkarim Bahadori; Mehdi Raadabadi; Mohamad Shariati (مجله ایرانی آموزش در علوم پزشکی, 2020)
Introduction: Academic engagement is one of the key factors related to the academic achievement of students, which is considered as a significant research issue in higher education. Academic engagement focuses on the internal commitment and active involvement of students in access to learning. This study endeavored to explore the relationship between academic engagement and achievement among nursing students of Ilam University of Medical Sciences. Methods: This cross-sectional descriptive was conducted in school of nursing in Ilam University of Medical Sciences. The population was all nursing students in 2018 (140 students) who completed and returned 116 questionnaires. The data collection instrument was a questionnaire taken from an external questionnaire including 14 questions in three dimensions of Vigor, Dedication, and Absorption. Besides, a researcher-made questionnaire was developed to measure students' academic achievement. Data was analyzed using descriptive statistics and correlation tests of Spearman, Manwitney and Kroskalwalis. Results: Among the dimensions of academic engagement, the dimension of Dedication (2.32±0.88) and Vigor (2.22±0.87) had the highest and lowest mean and standard deviation, respectively. There was no significant correlation between academic engagement and students' academic achievement (r=0.096). There was a significant relationship between gender with academic achievement and engagement and the years spent studying with students' academic involvement P <0.05). Conclusion: There was no significant correlation between the dimensions of academic engagement and Grad Point Average and the rate of academic engagement in female students was higher and decreased with age and increased the length (years) of study. It is suggested that interesting and varied methods need to be used for teaching and learning students. Similarly, holding training courses for professors to gain more skills in motivational management of students and learning attractive and effective teaching methods seems to be needed to promote students' academic engagement.